Sosialisasi Penerapan Manajemen Puskesmas dalam Rangka Meningkatkan Mutu Pelayanan di Puskesmas Kota Padang Tahun 2024 - Asyari, Dian Paramitha; Azkha, Nizwardi; Anshari, Luthfil Hadi (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
Community Health Centers (Puskesmas) are primary healthcare institutions at the forefront of providing healthcare services to the community. In Padang City, Puskesmas play a crucial role in public health services. The purpose of this community outreach activity is to provide information on the implementation of Puskesmas management, which is expected to provide solutions to various existing problems and bring positive changes in improving the quality of healthcare services at Puskesmas. The activity was conducted at two Puskesmas in Padang City in January 2025. The results of the outreach and evaluation showed that after the outreach, 85% of participants had a better understanding of Puskesmas governance, compared to 40% before the activity. The implementation of service quality standards also improved, particularly in service efficiency, patient satisfaction, and digital medical record management. Services that previously faced administrative constraints and limited human resources began to improve, with increased queuing system effectiveness and accelerated patient service times. In addition, the use of technology in digital medical record recording began to be implemented at several Puskesmas involved in this program. This facilitates patient data recording and increases efficiency in storing medical information.